Hubungan Disiplin Berlatih dan Kecemasan Kompetitif dengan Prestasi Atlet Karate PPLOP Jawa Tengah (MAN Insan Cendekia Jambi, 2026)
This study was designed to investigate the influence of training discipline and competitive anxiety on the performance of PPLOP karate athletes in Central Java, both individually and in combination. The study was conducted using a quantitative approach with a correlational design. The sample consisted of 11 PPLOP karate athletes from Central Java, selected using total sampling. The research instruments consisted of a training discipline questionnaire, the Competitive State Anxiety Inventory-2 Revised (CSAI-2R) used to measure competitive anxiety, and documentation of match results as data on the athletes’ performance. Data analysis utilised descriptive statistics, namely the Shapiro-Wilk normality test, Spearman’s rank correlation test, and ordinal regression. Based on the research results, there was no significant relationship between training discipline and athlete performance (r = -0.204; p = 0.548). Furthermore, competitive anxiety also had no significant relationship with athlete performance (r = -0.045; p = 0.897). The results of the ordinal regression analysis showed that training discipline and competitive anxiety, taken together, did not have a significant effect on athletic performance (p > 0.05). It is concluded that the performance of PPLOP Central Java karate athletes is influenced not only by training discipline and competitive anxiety, but also by other factors such as physical condition, technique, competition experience, and training strategy.